PENGUNGKAPAN INFORMASI PADA WEBSITE: STUDI TENTANG AKUNTABILITAS PENDIDIKAN PADA PERGURUAN TINGGI DI INDONESIA - Yuhertiana, Indrawati (Jurnal Strategi Akuntansi, 2011)
Good University Governance is very urgent and need to be implemented. As a place where people learn and build the concept of good governance itself, university need to make all of their operarional learning process being transparant and accountable. This reseach is evaluating any kind of website information disclosure related to the learning process ie tri dharma, the process of teaching, research, and community concern, include its financial disclosure. Qualitatve paradigma with document analysis is used in scrutinized 10 of the webometrics university rank in Indonesia. It is found that website still used as marketing tools of promotion for capturing the market so the conten information in university website stilll related to the program, reseaxrh and commnuity concern. It is difficult to find university financial report. Some university only expose their financial policy. But all of the research object have inform their vision, mssion, objectives, and brief of organization as a part of their strategic plan Keywords : akuntansi pendidikan, good university governance, website.